Phytochemical screening and antibacterial activity test of Curcuma zedoaria, C. aeruginosa, and C. mangga extracts against Aeromonas hydrophila - ADE DWI SASANTI; WIDANARNI WIDANARNI; SUKENDA SUKENDA; DINAMELLA WAHJUNINGRUM; MUNTI YUHANA; MIA SETIAWATI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Sasanti AD, Widanarni, Sukenda, Wahjuningrum D, Yuhana M, Setiawati M. 2025. Phytochemical screening and antibacterial activity test of Curcuma zedoaria, C. aeruginosa, and C. mangga extracts against Aeromonas hydrophila. Biodiversitas 26: 1573-1580. The chemical compounds found in plants, with their potent antibacterial properties, hold significant potential as alternatives to antibiotics. This study aimed to identify the compounds present in the extracts of C. zedoaria or zedoary, C. aeruginosa, pink and blue ginger, and C. mangga or mango turmeric and to test their antibacterial activity against A. hydrophila. The extract of C. zedoaria, C. aeruginosa, and C. mangga extracts were obtained by maceration in 70% ethanol at a solvent ratio of 1:5 (w/v). The compounds in the extracts were identified by phytochemical analysis, followed by Gas Chromatography-Mass Spectrometry (GC-MS) analysis. The extraction results showed extract yields of C. zedoaria 9.87% (w/w), C. aeruginosa 9.89% (w/w), and C. mangga 9.56% (w/w), respectively. The phytochemical analysis revealed that C. zedoaria extract contained the highest levels of flavonoids as quercetin and curcumin, compared to other extracts. The highest total flavonoids, tannins, saponins, and total phenolic compound contents were found in the C. aeruginosa extract, whereas the highest antioxidant content was found in the C. mangga extract. GC-MS analysis detected the compound 1,2,3-propanetriol with the highest percentage area in C. zedoaria extract; in C. aeruginosa extract, the highest percentage area was found in the neocurdione compound. In comparison, in C. mangga extract, the highest percentage area was found in (E)-Labda-8(17), 12-dien-15, 16-dial compound. All three extracts showed significant antibacterial activity against A. hydrophila, as indicated by the inhibition zone of 9.37 to 14.40 mm. The Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) against A. hydrophila of the three extracts were 6.25 mg mL-1 and 50 mg mL-1, respectively, suggesting their potential as new antibacterial treatments.